Penerapan Pendekatan Stem Dalam Edukasi Budidaya Lebah Madu Bagi Komunitas Tuli-Dengar Di Raya Honey Sebetan - Sumandya, I Wayan; Gde Iwan Setiawan; A A Istri Mirah Dharmadewi (LPPM Universitas HKBP Nommensen, 2025)
The beekeeping of Trigona laeviceps honey bees has high economic and ecological potential; however, in the Raya Honey Sibetan Deaf-Hearing Community, traditional methods are still practiced, resulting in low productivity and product quality. This community service activity aimed to enhance technical skills, STEM knowledge, and honey production capacity through the application of STEM-based beekeeping box installation technology and honey harvesting tools designed to be inclusive. The target partner group consisted of 11 members. The implementation methods included (1) program socialization and needs assessment; (2) training on STEM concepts in beekeeping and the use of technology; (3) mentoring and productivity evaluation; and (4) sustainability planning through cadre development and strengthening marketing networks. The results showed an increase in the average understanding of the program’s objectives from 46.3% to 81.8%, STEM knowledge scores from 41.5% to 87.2%, and beehive box assembly skills from 18.2% to 100%. Average honey productivity reached 198.4 ml per box, with a bee population growth rate of +24.6% and a 90.9% success rate in using the technology. The integration of a STEM approach based on visual communication and hands-on practice effectively improved the technical skills, productivity, and economic independence of the Deaf-Hearing community. This service model has the potential to be replicated in other special-needs communities with technological adaptations to suit the local context.